Developmental stage and cellular context determine oncogenic and molecular outcomes of Ezh2Y641F mutation in hematopoiesis - Sarah M. Zimmerman; Samantha J. Procasky; Sofia R. Smith; Jie-Yu Liu; Chad Torrice; George P. Souroullas (Blood Neoplasia)
Abstract: Mutations in the histone methyltransferase enhancer of zeste homolog 2 (EZH2), particularly the neomorphic Y641F hot spot mutation, are implicated in hematologic malignancies. However, how developmental timing and cellular context influence their oncogenic potential remains poorly understood. Here, we used a conditional Ezh2Y641F allele with multiple tissue-specific Cre drivers to investigate the effects of these mutations across hematopoietic development. We found that ubiquitous or early expression of Ezh2Y641F led to bone marrow failure and reduced survival with no evidence of transformation. In contrast, expression in committed B cells using CD19-Cre consistently induced B-cell lymphomas, underscoring a context- and stage-specific requirement for transformation. Transcriptomic analysis of B-cell progenitors revealed distinct gene expression changes between Cre models, including interferon signaling and upregulation of guanylate-binding proteins (GBPs) in Mx1-Cre Ezh2Y641F mutants. We identified a redistribution of histone 3 lysine 27 trimethylation at the GBP locus and showed that GBP2 overexpression impairs multilineage hematopoiesis by promoting apoptosis and skewing differentiation. These findings demonstrate that the oncogenic potential of Ezh2Y641F is highly dependent on the cellular environment in which it is expressed and that the timing of mutation acquisition critically shapes the impact of EZH2 on hematopoiesis and disease outcome.